Food-processing ground stone tools in the Greek Neolithic and Bronze Age. A synthesis of the published data - Bekiaris, Tasos; Chondrou, Danai; Ninou, Ismini; Valamoti, Soultana-Maria (Journal of Greek Archaeology, 2020)
Ever since the Paleolithic, the use of stone tools comprises one of the fundamental methods for the processing of plants (domesticated or not) and their transformation into edible substances. After many years of neglect, food-processing stone tools, such as grinding slabs and grinders (henceforth grinding tools), mortars and pestles (henceforth pounding tools), usually attributed to the wider technological categories of ‘ground stones’ or ‘macrolithics’, have finally gained a prominent position within the archaeological discipline. Especially during recent decades, several studies have demonstrated the analytical potential of these technological products towards the approach of past technological practices, economic strategies and social relations. The interpretive dynamics of prehistoric grinding and pounding tools were further informed by significant developments in the methodological field. Rigorous macroscopic studies, discussing the whole use-lives of these artifacts or aspects of them, as well as several microscopic studies, such as petrographic, use-wear and plant micro-remains analysis (i.e., phytoliths and starches), but also experimental and ethnoarchaeological research have further highlighted the vital role of these implements for prehistoric societies.